Absence, silence, and the shades of Takemitsu’s Ma in Venice - Lanuza Rilling, Felipe (Interstices: Journal of Architecture and Related Arts, 2019)
I propose to set up a dialogue between absence and silence; in particular, between my own interpretations of absence through layered images, and silence as it features in the musical works by Tōru Takemitsu. My layered images seek to re-present experiences of absence, as they appear to the senses in the built environment, responding to its capacity to evoke multiple, uncertain and distant presences that seem to be away from our grasp. In Takemitsu’s multi-layered and unstructured pieces, silence plays a key role in bringing about “ma” – a meaningful spatio-temporal gap or in-between condition with metaphysic connotations, of great significance in Japanese culture. Following a hint by composer Philip Dawson, and largely driven by intuition, I explore the –albeit distant– resonances of my visual work in the acclaimed Japanese composer’s music. In this way, I expand the interpretative possibilities of absence and layering in representing the vanishing atmospheres of Venice, an example of fragile existence and aggregated formation.